Analisis Kepuasan Mahasiswa Terhadap Laporan Kualitas Pelayanan Lab Komputer Dengan Metode Importances Perfomances Analysis (IPA) - Sefnath Ambram Taran (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2024)
This research aims to analyze student satisfaction with computer laboratory services at STMIK WIDURI using the Importance Performance Analysis (IPA) approach. This investigation found that the quality of service received by students did not meet expectations. High priority, high quality equipment, laboratory technician workshop, services accessible to students, availability of laboratory technicians, easy access to laboratory technicians. STMIK WIDURI Analysis of student satisfaction with computer practicum is expected to increase priorities for the first quarter.